The Mediating Effect of Resilience in The Relationship Between Work Overload and Job Burnout among Teaching Accountants - Indudewi, Dian; Prihantini, Febrina Nafasati; Pribadi, Agung Santoso; Susanto, Barkah (International Journal of Economics Development Research (IJEDR), 2023)
High demand for performance provokes burnout among teaching accountants. As educators, teaching accountants must fulfill three pillars of higher education: educating students, doing research and community service. As professionals, teaching accountants may have a role as auditor or holding a structural position in the university. This study examines resilience as a mediator between work overload and burnout. This study used voluntary sampling and the questionnaires distributed via Google Forms. Seventy-one questionnaires have been received and are amenable to analysis using Smart PLS 4. The testing phase commences with descriptive statistics and quality tests of the instruments, including validity and reliability, before advancing to structural model testing. The findings reveal that work overload exerts a positive impact on job burnout. Furthermore, resilience has been substantiated as a mediator between work overload and job burnout.